Study of Feasibility on Broiler Business Development - nining haryuni (Journal of Development Research, 2017)
The method used in the article writing here is a review of several journals related to the development of broiler farming patterns. The purpose of writing this article is to know the advantages, disad-vantages and financial analysis of broiler development patterns independently and patnership system. Financially analyzed results obtained Day Old Chick input price (DOC) on partnership system 9,52% higher than independent system. The feed price on independent systems is relatively cheaper than the partnership system where the feed price difference is about 1000, - / kg of feed. The total revenue earned by independent farmers is 6,25% higher than the partnership system. BEP (Break Event Point) in the partnership system is relatively larger than the independent system. The R/C ratio analysis of independent system pattern is more advantageous than the partnership system where the independent system obtained R / C ratio of 1.31 and the partnership system of 1.11.